Counter-terrorism legislation and terrorist attacks: Does human rights have space? - Bretas, Heloisa Tenello [UNESP]; Damásio Borges, Daniel [UNESP] (Centro de Ensino Unificado de Brasilia, 2018)
The proposed theory for this study argues that terrorist attacks affect people's perception of security, creating an intense sensation of fear that leads to the support of repressive measures to counter terrorism. Evaluating United States before and after 9/11, this study found that terrorist attacks result in intense perception of danger and a consequent sensation of fear. In turn, this fear led to the support of relaxation of due process, sacrifice of civil liberties in exchange of security, and torture. The legislation analysis presented relaxation of due process rights, especially with the acceptance of illegal evidence, the only indicator that followed the causation process here proposed. Even though it was not found strong support for the theory, the study presents that the fear populations experience after terrorist attacks is connected with high support for the assassination of suspects of terrorism, which was a real surprise. Therefore, campaigns like #wearenotafraid, are interesting mechanisms to be propagated in order to reduce the sensation of insecurity among citizens and to maintain a certain rationality to calculate the costs and benefits of the measures proposed, not accepting undue restrictions.
Keywords: Counter-terrorism Legislation; Fear; Human Rights; Security; Terrorism